Interface morphology driven exchange interaction and magnetization reversal in a Gd/Co multilayer. Issue 11 (2nd March 2022) - Singh, Surendra; Basha, M. A.; Bhatt, Harsh; Kumar, Yogesh; Gupta, M.
Abstract : A correlation of the interface structure and magnetization of a Gd/Co multilayer upon annealing at 573 K. Abstract : Rare-earth (RE)/transition metal (TM) ferromagnetic heterostructures with competing interfacial coupling and Zeeman energy provide a rich ground to study different phase states as a function of magnetic field and temperature. The interface morphology as a knob in these RE/TM heterostructures provides an excellent opportunity to engineer the macroscopic magnetic response by tuning the interface dependent microscopic interactions between the layers. We have investigated the interface morphology driven structure and magnetic properties of a Gd/Co multilayer. The interface morphology of the multilayer was controlled by annealing the multilayer at a relatively low temperature of 573 K under vacuum conditions. Combining the different experimental techniques and a simple one-dimensional spin-based model calculation, we studied the detailed magnetic structure and magnetization reversal mechanism in this system across compensation temperature ( T comp ), which suggested a strong interface dependent coupling in the system. We showed that changes in the interface morphology of the Gd/Co multilayer strongly influence the macroscopic magnetic properties of the system. The calculation also confirms the formation of a helical magnetic structure with a 2π domain wall in this system below T comp . The experimental finding and the simulation of this technologically important system will help to understand the physics of all-optical switching and related applications.